DEPRESSION AMONG STUDENTS AT THUYLOI UNIVERSITY - Lê, Công Thiện; Nguyễn, Văn Tuấn; Nguyễn, Thành Long; Đào, Ngọc Ánh; Phùng, Trần Thu Hằng; Phạm, Thị Hiền; Vũ, Thị Mỹ Hạnh; Cao, Thị Ánh Tuyết; Nguyễn, Đình Trinh (Tạp chí Sinh lý học Việt Nam, 2022)
Background: In recent years, the rate of population suffering from depression is increasing, especially depression in adolescents aged 14-29 years old. We found that no study measures the depression in students at ThuyLoi university, so we want to measure it. Subjects and methods: A cross-sectional study was conducted among students of ThuyLoi university. Result: Our study shows that depression by DASS 21 among the 2478 students, 14.2% of students participating in the interview experience major depression problems; 9.4% of students had moderate depression and 7.6% of students had mild depression. First year students, girl students, and students with childhood trauma have a higher percentage of having depression than other groups. Conclusion: Thus, through the results of practical research, we found that: the number of students with psychological problems, especially mild to very severe depression, accounts for nearly half of the students participating in the interview. This shows that this is a very urgent issue in universities in general and ThuyLoi University in particular. University should coordinate with medical facilities to regularly and timely advises students on psychological issues to improve the quality of students' health in the most comprehensive way.